Analysis of the natural ventilation performance of residential areas considering different urban configurations in Elaz, Turkey - Gulten, Ayca; Öztop, Hakan Fehmi (Elsevier, 2020)
Internal morphology and contextual background of the cities are the main factors affecting the natural ventilation ability of an urban district. Spatially-averaged wind velocity ratio became a remarkable parameter in order to evaluate the ventilation efficiency of an urban area. This work focuses on the comparison of four different urban configurations densely exist in Elaz, a city in east side of Turkey based on spatially-averaged wind velocity ratio by using a computational analysis. Wind velocities of points on defined axises of each configuration were also measured to control the accuracy of relation between urban configuration and wind velocity ratio. Four different urban configurations that represent generic layouts of old residential areas were assessed in Elaz as A, B, C, and D. Configuration D, presents a layout with a courtyard in the middle of the residential blocks while the buildings in other configurations stand separately. Residential buildings in Configurations A and B generally have a square plan layout while configuration C consists of long rectangular shaped building plan layouts. The Computational Fluid Dynamics (CFD) 3-D steady-state simulations were completed to assess urban configurations that consider wind velocities of 2, 3, and 5 m/s with 0 degrees, 45 degrees. and 90 degrees wind directions. As a result, configurations rated from highest to lowest ventilation performance as Conf. B, Conf. A, Conf. D, and Conf. C while parameters can be rated from most to least as i)urban configuration, ii)wind direction and iii)wind velocity in terms of their effect on ventilation efficiency.
Keywords: Urban ventilation; Urban configuration; Spatially-averaged wind velocity ratio cfd